The Influence of Competence and Experience of Auditors on Audit Outcomes - Mustika, Lani (Manunggal Halim Jaya, 2023)
This qualitative study investigates the influence of auditor competence and experience on audit outcomes in the realm of financial governance. The research aims to explore the lived experiences and perceptions of auditors, clients, and other stakeholders regarding these critical attributes. Adopting a phenomenological approach, data was collected through semi-structured interviews and focus group discussions with purposively sampled participants. Thematic analysis revealed key insights into auditor competence and experience. Competent auditors were found to possess advanced technical skills, critical thinking abilities, and professional judgment, enabling them to navigate complex audit engagements effectively. Meanwhile, experienced auditors were noted for their deep understanding of industry nuances, client operations, and regulatory requirements, contributing to audit effectiveness and reliability. The interplay between competence and experience emerged, highlighting their symbiotic relationship in enhancing audit quality. The findings underscore the importance of continuous learning and development initiatives to maintain auditor competence and the need for diverse audit experiences to accumulate valuable experiential knowledge. This study sheds light on the multidimensional nature of auditor competence and experience and their profound impact on audit outcomes, providing valuable insights for auditing practices and regulatory frameworks.